Dynamical gluon mass corrections in heavy quarkonia decays - Mihara, A.; Natale, A. A. (Elsevier B.V., 2000)
Using the expression of the dynamical gluon mass obtained through the operator product expansion we discuss the relevance of gluon mass effects in the decays V --> hadrons (V = J/psi, Y), Relativistic and radiative corrections are also introduced to calculate alpha(s)(m(c)) and alpha(s)(m(b)) comparing them with other values available in the literature. The effects of dynamical gluon masses are negligible for Y decay but important for J/psi decay. (C) 2000 Elsevier B.V. B.V. All rights reserved.